Designing polylibraries to speed up linear algebra computations. (8th August 2005) - Alberti, Pedro; Alonso, Pedro; Vidal, Antonio M.; Cuenca, Javier; , Domingo Gimenez
In this paper, we analyse the design of polylibraries, where the programs call for routines from different libraries according to the characteristics of the problem and of the system used to solve it. An architecture for this type of library is proposed. Our aim is to develop a methodology which can be used in the design of parallel libraries. To evaluate the viability of the proposed method, the typical linear algebra libraries hierarchy has been considered. Experiments have been performed in different systems and with linear algebra routines from different levels of the hierarchy. The results confirm the design of polylibraries as a good technique for speeding up computations.